2021
DOI: 10.3390/ijerph18126567
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Utility of Changes in Optic Nerve Sheath Diameter after Cardiac Arrest for Neurologic Outcomes

Abstract: The optic nerve sheath diameter (ONSD) can help predict the neurologic outcomes of patients with post-cardiac arrest (CA) return of spontaneous circulation (ROSC). We aimed to investigate the effect of ONSD changes before and after CA on neurologic outcomes in patients with ROSC after CA using brain computed tomography (CT). The study included patients hospitalized after CA, who had undergone pre- and post-CA brain CT between January 2001 and September 2020. The patients were divided into good and poor neurolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We found a large variance in ONSD measurements, which might be partly caused by human variability. This problem could be overcome by looking at changes of ONSD relative to pre-cardiac arrest ONSD [ 27 ]. Nonetheless, pre-cardiac arrest ONSD is usually not available.…”
Section: Discussionmentioning
confidence: 99%
“…We found a large variance in ONSD measurements, which might be partly caused by human variability. This problem could be overcome by looking at changes of ONSD relative to pre-cardiac arrest ONSD [ 27 ]. Nonetheless, pre-cardiac arrest ONSD is usually not available.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the TTM rate may have affected the neurological outcomes of patients. Third, in healthy adults, there are differences in the baseline ONSD according to individual characteristics including sex, body mass index (BMI), race, or eyeball size [ 34 , 35 , 36 ]. Most studies conducted on healthy volunteers have demonstrated varying mean or median ONSD values across study cohorts, depending on race or measurement tools [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes of the optic nerve sheath (as in optic neuritis, multiple sclerosis and vasculitis) can cause perineural edema that increases the ONSD [30,31]. Additionally, since the ONSD can vary from person to person, the ONSD may not fully reflect the IICP [32]. Thus, using the ONSD measurement in isolation to predict a poor outcome is unwarranted, and it should only be used as one test within a multimodal prognostic approach.…”
Section: Discussionmentioning
confidence: 99%